Empty chair technique for stress reduction in high school adolescents: a quasi-experimental investigation using the perceived stress scale - Laili Alfita; Siti Aisyah (Jurnal Konseling dan Pendidikan, 2025)
This study examined the efficacy of the empty chair technique in reducing stress levels among stressed female adolescents in secondary education settings. A quasi-experimental, one-group pretest-posttest design was employed. The sample comprised 74 high school female students selected through purposive sampling based on pre-established stress symptomatology criteria. Psychological distress was assessed using the Perceived Stress Scale (PSS-10), a 10-item unidimensional instrument with demonstrated validity (Cronbach's α = 0.81) and internal consistency across adolescent populations. The empty chair technique intervention was administered across 8 weekly sessions (60-minute duration per session), conducted by trained Gestalt counselors following manualized protocol. Data were analyzed using paired-samples t-tests with calculation of Cohen's d effect sizes and 95% confidence intervals. Mean perceived stress scores decreased significantly from pretest (M = 18.59, SD = 9.18) to posttest (M = 15.85, SD = 9.57), representing a reduction of 2.74 points (95% CI: 1.32–4.16). Paired-samples t-test revealed this reduction was statistically significant, t(73) = 2.91, p = 0.004, with a moderate effect size (Cohen's d = 0.29). The magnitude of change suggests clinically meaningful stress reduction, as approximately 68% of participants demonstrated measurable improvement exceeding one standard error of measurement. The Empty Chair Technique demonstrates efficacy as a school-based, brief psychosocial intervention for reducing psychological stress among adolescents. Future investigations should employ randomized controlled designs with longer follow-up assessments, standardized adherence measures, and multi-method outcome evaluation to establish robust evidence for dissemination within school counseling programs.